Blur detection of digital forgery using mathematical morphology - Hui-fen HUANG; Zhi-hong WANG; Yu-hong CHANG (网络与信息安全学报)
Aiming at the fuzzy operation commonly used in image tampering,a new fuzzy detection scheme using smooth filter preserving edges and mathematical morphological methods was studied.By using the sharpening function and denoising function of both methods,tampering and location of tampering position can be pointed out without embedding information such as watermarking technique.The method can not only determine whether an image has been virtualized,but also detect the extent of the image blur.Experimental results confirm the effectiveness of the scheme.